A SURVEY ON BIG DATA: INFRASTRUCTURE, ANALYTICS, VISUALIZATION AND APPLICATIONS - Saraswathi, Selliah; Deepa, Ganesan; Vennila, Ganesan; Parthasarathy, Sudhaman; Ramadoss, Balakrishnan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Big data is a collection of heterogeneous and autonomous data sources which are available abundantly in multiple formats. Knowledge discovery and decision-making from the ever-growing abundant data are challenging tasks for data-oriented business organizations. Big data analytics investigates a large amount of data to find correlations among the available data and finally provides useful information to business organizations. Big data analytics facilitates application domains such as business, banking, healthcare, transportation, social media, agriculture, and government sectors. Existing surveys on big data are based on either of the following dimensions: characteristics, analytics, and visualization, or discuss the applications of big data analytics in the field of agriculture, transportation, etc., separately. However, this article provides a survey of big data, which integrates different dimensions of big data, such as infrastructure, analytics, visualization, and their applications. It also discusses the technologies and tools involved in the domains mentioned above.